Penerapan Problem Based Learning (PBL) dalam Meningkatkan Hasil Belajar Siswa Kelas X-4 SMAN 1 Babat - Dwi Karunia Dhamar Panuluh; Rr Nanik Setyowati; Faizatul Amilin; Ika Setia Rini (Journal on Education, 2023)
This research was conducted with the aim of improving the learning outcomes of class X-4 SMA Negeri 1 Babat in the subject of Pancasila Education, by applying the Problem Based Learning (PBL) learning model. This research used a type of classroom action research (PTK) which was conducted in two cycles, with two meetings in each cycle. Each cycle consists of planning, action, observation, and reflection stages. The main material discussed in the first and second cycles is regarding the role and position of Indonesian citizens. The subjects of this study were 37 students of class X-4 of SMA Negeri 1 Babat for the 2022/2023 academic year. The main data collection techniques in this study were tests and observations, while the supporting techniques were interviews and documentation. The results of the study concluded that the application of the Problem Based Learning (PBL) learning model could improve the learning outcomes of class X-4 SMA Negeri 1 Babat in the subject of Pancasila Education. This can be seen from the increase in student learning outcomes from the pre-action stage (67.65) to 75.65 in cycle I and increased again to 85.40 in cycle II. Therefore, it can be concluded that the application of the PBL learning model can be effective in improving student learning outcomes in the Pancasila Education subject.